The Impact of Transformational Leadership of CEOs and Organizational Health of Private Higher Education Institution Academicians in Malaysia. (Journal of Basic and Applied Research in Biomedicine, 2022)
This study aimed to determine the level of transformational leadership practices by PHEIs CEO’s in the state of Selangor, Malaysia. The four dimensions of transformational leadership studied were individual consideration, intellectual stimulation, inspirational motivation and idealized influence. The study also looks at the level of lecturers’ job satisfaction as well as the relationship with the practice of transformational leadership style by the CEOs. The respondents consisted of 465 lecturers employed in 15 PHEIs in the Klang Valley district, Selangor. The data obtained was analyzed using SPSS version 20.0. Descriptive analysis and Pearson Correlation Coefficient were used to analyze the strength of the relationship. The results provided an extent of support to the main hypothesis; CEOs that practiced transformational leadership do have an impact on the job satisfaction of lecturers. Main implications are discussed and directions for future research are also provided.